The significance of government support towards entrepreneurship development of the Hausa people in Nigeria - Abdul Aziz, Abdullah; Ibrahim Tijjani, Sabiu (2019)
Entrepreneurship plays an important role in the process of economic development, and has remained vital concept adopted for social, economic and human development. However, the Hausa people of northern Nigeria are said to be the most impoverished people with several socio-economic inequalities existing between them and other ethnics in Nigeria. Therefore, entrepreneurship development strategy appears to be one of the most suitable strategies for economic development of less developed societies, as it is less costly and more appropriate for the less developed people. Similarly, to create an entrepreneurship environment, several stakeholders take a vital function in stimulating entrepreneurship. Hence, this paper highlighted the significance of government support towards the entrepreneurship development of the Hausa people. This conceptual paper has gone through an extensive process in identifying issues bedeviling Hausa entrepreneurs in Nigeria, types of government supports available to them, loopholes identified in the government support, and gap existing in the entrepreneurship development of Hausa people in Nigeria. Therefore, the paper has further suggested some recommendations for expediting the progress of the development of the entrepreneurship of Hausa people, and fixing the leakages in the government support, while making a huge impact to the economy in general.